2014
DOI: 10.1002/ppap.201400059
|View full text |Cite
|
Sign up to set email alerts
|

Long, Vertically Aligned Single-Walled Carbon Nanotubes from Plasmas: Morpho-Kinetic and Alignment Controls

Abstract: The enhanced large‐scale model and numerical simulations are used to clarify the growth mechanism and the differences between the plasma‐ and neutral gas‐grown carbon nanotubes, and to reveal the underlying physics and the key growth parameters. The results show that the nanotubes grown by plasma can be longer due to the effects of hydrocarbon ions with velocities aligned with the nanotubes. We show that the low‐temperature growth is possible when the hydrocarbon ion flux dominates over fluxes of other species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 73 publications
(144 reference statements)
1
11
0
Order By: Relevance
“…More recently, Burmaka et al 15 have shown that the growth rates of SWCNT array and the film between the nanotubes, as well as the length of SWCNTs can be successfully controlled by adjusting neutral and ion fluxes to the nanotubes, SWCNT surface temperature and the penetration depths of the neutral and ionic species.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, Burmaka et al 15 have shown that the growth rates of SWCNT array and the film between the nanotubes, as well as the length of SWCNTs can be successfully controlled by adjusting neutral and ion fluxes to the nanotubes, SWCNT surface temperature and the penetration depths of the neutral and ionic species.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous works have been done to highlights the role of temperature on the growth of CNTs. [8][9][10][11][12][13][14][15] Han et al 8 have demonstrated that as the growth temperature increases, the average diameter of CNTs increased from 40 to 110 nm and the growth rate was enhanced from 2 to 15 lm/h. Baratunde et al 9 have shown that as the growth temperature was decreased, the associated decrease in CNT density and average CNT diameter resulted in an increased thermal resistance at the interface.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the known techniques to grow carbon nanostructures, CVD in a plasma medium is prominent owing to the low‐temperature growth of nanostructures, good control over the morphology, and process parameters . In a plasma‐enhanced CVD (PECVD) process, the energetic electrons in the plasma enhance the ionization, excitation, and dissociation of hydrocarbon precursors at relatively low temperature .…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructure growth characteristics can be controlled by the proper selection of the plasma parameters. Studies have been carried out to investigate the effect of radiofrequency power, feedstock gas ratio, hydrogen gas, and growth time, and so forth on the structure, growth rate, and dimensions of the CNT and graphene …”
Section: Introductionmentioning
confidence: 99%